The Human Factor in the Development of Innovations in the Context of Globalization - Adilov Botir Baltabayevich; Abdullayeva Madina Kamilovna; Shodiev Toxir Ochilovich (Zien Journals, 2022)
The issues related to the human factor and its activation in innovative development play an important role in the development of programs for socio-economic development of the country, the deepening of reforms. This article provides views on the development of competitive training for innovation in the context of globalization, increasing the prestige of scientific work, as well as scientifically based recommendations for capacity building.
Keywords: national economy; national education system; innovative development; human capital